In Vitro and In Vivo Evaluation of Inhalable Ciprofloxacin Sustained Release Formulations - Changzhi Shi; Kewei Guo; Li Zhang; Yi Guo; Yu Feng; Sandra Cvijić; Dongmei Cun; Mingshi Yang (MDPI AG, 2023)
Respiratory antibiotics delivery has been appreciated for its high local concentration at the infection sites. Certain formulation strategies are required to improve pulmonary drug exposure and to achieve effective antimicrobial activity, especially for highly permeable antibiotics. This study aimed to investigate lung exposure to various inhalable ciprofloxacin (CIP) formulations with different drug release rates in a rat model. Four formulations were prepared, i.e., CIP-loaded PLGA micro-particles (CHPM), CIP microcrystalline dry powder (CMDP), CIP nanocrystalline dry powder (CNDP), and CIP spray-dried powder (CHDP), which served as a reference. The physicochemical properties, drug dissolution rate, and aerosolization performance of these powders were characterized in vitro. Pharmacokinetic profiles were evaluated in rats. All formulations were suitable for inhalation (mass median aerodynamic diameter < 5 µm). CIP in CHPM and CHDP was amorphous, whereas the drug in CMDP and CNDP remained predominantly crystalline. CHDP exhibited the fastest drug release rate, while CMDP and CNDP exhibited much slower drug release. In addition, CMDP and CNDP exhibited significantly higher in vivo lung exposure to CIP compared with CHDP and CHPM. This study suggests that lung exposure to inhaled drugs with high permeability is governed by drug release rate, implying that lung exposure of inhaled antibiotics could be improved by a sustained-release formulation strategy.